Ulnar collateral ligament injuries of the elbow in female division I collegiate gymnasts: a report of five cases - Nicolette, G. W.; Gravlee, J. R. (Open Access Journal of Sports Medicine, 2018)
Introduction: Elbow ulnar collateral ligament (UCL) injuries in gymnastics have not been well documented in the literature, in comparison to UCL injuries in baseball. Few studies have examined the mechanism and nonoperative management of this injury, and no studies to date have been published on incidence of injury and return to play recommendations in gymnastics. Patient case review: A literature search was performed using PubMed to review articles from 1980 to 2016 that addressed the biomechanics of UCL injury in baseball and gymnastics, the anatomy of the elbow, injury rates, surgical vs non-surgical management, rehabilitation, and return to play recommendations for the sport of gymnastics. Five female collegiate gymnasts sustained UCL injury over a 3-year period. Electronic medical records for each case were thoroughly reviewed including imaging, surgical and non-surgical management, rehabilitation, and the progressive return to gymnastics. Discussion: Four UCL injuries were confirmed by MRI to be avulsions at the distal insertion of the UCL and one was an avulsion at the proximal origin. While less than half of baseball players can return to competition with conservative management of these types of injuries, four out of five gymnasts were able to return to competition with nonoperative management. One gymnast opted to have reconstruction after a successful competition season. Time to return to play varied seemingly dependent on the severity of UCL injury and event. Conclusion: In our case series, collegiate female gymnasts were able to return to participation with nonoperative treatment of the UCL. Their success in returning to competitive gymnastics may also depend on the event(s) in which they are trying to participate. Strength of Recommendation Taxonomy: C.